Recent Progress in the Synthesis of Benzoxazin-4-Ones, Applications in N-Directed Ortho-Functionalizations, and Biological Significance - Ziad Moussa; Mani Ramanathan; Harbi Tomah Al-Masri; Saleh A. Ahmed (Molecules)
The development of efficient synthetic procedures to access fused N, O-heterocyclic skeletons has been a pivotal research topic in organic synthesis for several years. Owing to the applications of N, O-fused heterocycles in organic synthesis, material sciences, and medicinal chemistry, significant efforts have been dedicated to design novel methods for their construction. To this end, 1,3-benzoxazin-4-ones are privileged candidates for N, O-heterocyclic molecules often found in natural products, agrochemicals, and materials science applications. In this review, we aim to summarize the existing literature on the synthesis of 1,3-benzoxazin-4-ones from 2010 onwards. Moreover, 1,3-benzoxazin-4-ones have also been identified as an excellent native directing group for the ortho-functionalization via C-H activation, which is often a strenuous task requiring pre-functionalized substrates. In the latter part of this report, we compiled several interesting examples of N-directed functionalizations of 1,3-benzoxazin-4-ones. Additionally, to emphasize biological importance, recent developments on the anticancer evaluations of benzoxazine-4-one core are included. We believe that by harnessing the methodologies discussed herein, new possibilities could be unlocked for the synthesis of fused N, O-heterocycles, leading to the development of novel biologically active compounds and functional materials.